Exostoma dulongensis, a new glyptosternine catfish from the Irrawaddy basin, Yunnan, China (Siluriformes: Sisoridae) - Luo, Zhaojun; Chen, Xiaoyong (Zootaxa, 2020)
Exostoma dulongensis sp. nov., a new species of sisorid catfish from the genus Exostoma Blyth, 1860, is described from the Xiaojiang River and Dulongjiang River, tributaries of N’mai Hka River in the Irrawaddy basin, Yunnan Province, China. Exostoma dulongensis sp. nov. is the seventeenth species reported within this genus and is most similar to Exostoma ericinum Ng 2018 in morphology but can be distinguished by the following characters: tip of pelvic fin far from anus vs. reaching when depressed; nasal barbel reaching or surpassing posterior edge of orbit vs. just reaching middle of orbit; greater preanal length (70.9%–80.1% SL vs. 67.7%–70.5%); and longer dorsal to adipose length (13.5%–23.8% SL vs. 8.0%–12.0%). The new species can also be distinguished from all known congeners by the following characters: adipose fin confluent with caudal fin and without incision; caudal fin weakly forked; 40–43 vertebrae; and pectoral fin extending to vicinity of dorsal fin origin.